Experimental verification between the functioning of tribosystems in the conditions of boundary lubrication - Voitov, A.V. (Problems of Tribology, 2022)
The paper presents an experimental test of modeling the limits of stable operation of different structures of tribosystems (robustness criteria) in the conditions of extreme lubrication. The results of the experimental test confirmed the previously concluded conclusion that not all structures of tribosystems lose stability in terms of the coefficient of friction, i.e. the appearance of burrs on the surfaces of the friction. At low values of the coefficient of shape and low values of the quality factor of the tribosystem, the loss of stability occurs due to accelerated wear of materials.Expressions for calculation of criteria of robustness of tribosystems taking into account speed of change of loading on tribosystem are received. The rate of change of load is taken into account by the coefficients of dynamism, which are obtained taking into account the right-hand side of the differential equation of the dynamics of the functioning of tribosystems. Analysis of the obtained theoretical results on the assessment of the robustness of tribosystems and their comparison with the results of the experiment, suggest that the obtained conditions for stable operation of tribosystems (criteria of robustness) allow theoretically, with error 10,3 - 13,3 %, determine the boundaries of sustainable work. Criteria for the robustness of the tribosystem by wear rate and friction coefficient should be used in the design of tribosystems.